ANALYSIS OF CUSTOMER SATISFACTION WITH DELIVERY SERVICE AT APOTEK HABIBI KUNINGAN - Jumiati, Juju; Djuniardi, Dede; Hanifah, Rakhmawati; Noviansyah, Ramadhan (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Improving service quality in the pharmacy business is crucial to attracting customer interest and maintaining customer loyalty. Customer satisfaction is one of the indicators that can be used to measure the success of service quality. This study aimed to determine the effect of delivery service quality on customer satisfaction in Apotek Habibi. This study used a descriptive observational method and a cross-sectional design. Purposive sampling was used, with the Slovin formula used to obtain 83 respondents from a total population of 497 people. Data were collected through a survey of customers who had used the delivery service at least thrice. Service quality was measured using five dimensions of the Servqual method: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results show that customers are highly satisfied with delivery service quality, with the highest scores in the Tangibles dimension (92%), Reliability (90%), Responsiveness (90%), Assurance (91%), and Empathy (89%). The Pearson's correlation analysis revealed a significant relationship between service quality and customer satisfaction (r = 0.537, p < 0.05). The Assurance variable emerged as the dominant factor influencing customer satisfaction with a regression coefficient of 10.810. Although customer satisfaction is high, developing a more flexible delivery system and improving promotional information transparency are necessary to maintain and enhance customer satisfaction in the future. This study provides valuable insights for Apotek Habibi to continuously improve service quality to meet customer expectations. Keywords: Pharmacy, Customer Satisfaction, Delivery Service, Service Quality